2020
DOI: 10.1155/2020/1907821
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy for the Treatment of Osteoarthritis: A Systematic Review and Meta-Analysis

Abstract: Background. Osteoarthritis is the most common musculoskeletal disease. Extracorporeal shockwave therapy had shown an effect on osteoarthritis in both some animal experiments and clinical studies, but there was no systematic review to confirm the value of shockwave therapy in the treatment of all types of osteoarthritis and compare it with other traditional therapies (especially traditional Chinese medicine). Method. PubMed, Medline, the Cochrane Central Register of Controlled Trials, Web of Science, Chinese Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 51 publications
2
35
0
2
Order By: Relevance
“…We found evidence to support the use of joint mobilization 66,67 for knee OA, and dry needling 36 in hip OA. In contrast, there was conflicting evidence for the use of laser therapy 26,32 for thumb OA, ECSW therapy 23,24,29,62 and kinesiotape 33,63,64 for hand and knee OA, therapeutic ultrasound 27,59 , and PEMF 25 for knee OA, and neurodynamic mobilizations 34 for hand OA. These findings reinforce existing guidelines 3 that suggest these interventions should only be considered as an adjunct, not standalone, treatments for persons with OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found evidence to support the use of joint mobilization 66,67 for knee OA, and dry needling 36 in hip OA. In contrast, there was conflicting evidence for the use of laser therapy 26,32 for thumb OA, ECSW therapy 23,24,29,62 and kinesiotape 33,63,64 for hand and knee OA, therapeutic ultrasound 27,59 , and PEMF 25 for knee OA, and neurodynamic mobilizations 34 for hand OA. These findings reinforce existing guidelines 3 that suggest these interventions should only be considered as an adjunct, not standalone, treatments for persons with OA.…”
Section: Discussionmentioning
confidence: 99%
“…This included one SR of guidelines 14 , one SR of SRs and meta-analyses 16 , and 16 SRs of RCTs (Table II). Interventions investigated included various individual (aquatic 19 , whole body vibration 22 , proprioceptive 21 , yoga 30 , resistance-based 20 ) or combined 14,16,18,28,31 exercisetherapies/physical activities, technologies (wearable activity trackers) 15 and behaviour change approaches 17 to improve adherence to exercise and physical activity (PA), and modalities (Extracorporeal Shockwave Therapy; ESWT 23,24,29 , Pulsed Electromagnetic Field Therapy; PEMF 25 , laser therapy 26 ; and therapeutic ultrasound 27 ).…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Emerging evidence supports ESWT as non-invasive therapy for OA [25], whereas data about the effectiveness of this physical modality for patients with EOA are lacking. Chou et al [13] have shown on animal models that ESWT has protective effects for joint tissues (i.e., articular cartilage, synovium, subchondral bone), delaying the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systemic review and meta-analysis studies have investigated the efficacy of ESWT in the treatment of KOA [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Most trials included in these reviews and meta-analysis studies conducted an ESWT intervention in combination with noninjection treatments such as conventional physical therapy (CPT) and traditional Chinese medicine (TCM).…”
Section: Introductionmentioning
confidence: 99%